A novel long non-coding RNA, DIR, increases drought tolerance in cassava by modifying stress-related gene expression - Shi-man DONG; Liang XIAO; Zhi-bo LI; Jie SHEN; Hua-bing YAN; Shu-xia LI; Wen-bin LIAO; Ming PENG (Journal of Integrative Agriculture, 2022)
Cassava is an important tropical cash crop. Severe drought stresses affect cassava productivity and quality, and cause great economic losses in agricultural production. Enhancing the drought tolerance of cassava can effectively improve its yield. Long non-coding RNAs (lncRNAs) are present in a wide variety of eukaryotes. Recently, increasing evidence has shown that lncRNAs play a critical role in the responses to abiotic stresses. However, the function of cassava lncRNAs in the drought response remains largely unknown. In this study, we identified a novel lncRNA, DROUGHT-INDUCED INTERGENIC lncRNA (DIR). Gene expression analysis showed that DIR was significantly induced by drought stress treatment, but did not respond to abscisic acid (ABA) or jasmonic acid (JA) treatments. In addition, overexpression of the DIR gene enhanced proline accumulation and drought tolerance in transgenic cassava. RNA-seq analysis revealed that DIR preferentially affected drought-related genes that were linked to transcription and metabolism. Moreover, RNA pull-down mass spectrometry analysis showed that DIR interacted with 325 proteins. A protein–protein interaction (PPI) analysis found a marked enrichment in proteins associated with the mRNA export and protein quality control pathways. Collectively, these results suggest that DIR and its interacting proteins that regulate mRNA or protein metabolism are involved in mediating the drought stress response. Thus, regulating DIR expression has potential for improving cassava yield under drought conditions.